1998
DOI: 10.1161/01.cir.98.17.1742
|View full text |Cite
|
Sign up to set email alerts
|

Improved Exercise Tolerance After Losartan and Enalapril in Heart Failure

Abstract: Six months' treatment with L and with E produces an improvement in EC of similar magnitude. These changes are accompanied by a reshift of MHCs of leg skeletal muscle toward the slow, more fatigue-resistant isoforms. Magnitude of MHC1 changes correlates with the net peak V(O2) gain, which suggests that improved EC may be caused by favorable biochemical changes occurring in the skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Indeed, we did not find improvement in grip strength over time. Given the broad influence of the RAS on many tissues, and the fact that ARBs such as losartan impact multiple organ systems, we can speculate that some of the observed activity improvement may come from ARB related cognitive and cardiovascular improvements and from mitochondrial functional improvement, in addition to skeletal muscle improvement 3;9;18 . Next, the broad array of activity measures that we utilized in this study are not necessarily measuring the same kind of activity that equipment with sensor beams such as the Opto-M4 (Columbus Instruments, Columbus, OH, USA) uses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we did not find improvement in grip strength over time. Given the broad influence of the RAS on many tissues, and the fact that ARBs such as losartan impact multiple organ systems, we can speculate that some of the observed activity improvement may come from ARB related cognitive and cardiovascular improvements and from mitochondrial functional improvement, in addition to skeletal muscle improvement 3;9;18 . Next, the broad array of activity measures that we utilized in this study are not necessarily measuring the same kind of activity that equipment with sensor beams such as the Opto-M4 (Columbus Instruments, Columbus, OH, USA) uses.…”
Section: Discussionmentioning
confidence: 99%
“…Losartan has already been demonstrated to accelerate muscle healing and slow the development of disuse atrophy in aging mice 8 . In addition, an earlier pilot study of chronic losartan treatment in humans with heart failure demonstrated improvement in exercise capacity associated with a shift towards more fatigue resistant skeletal muscle fibers 9 . Although multiple hormonal and pharmaceutical treatments have been developed for age-related sarcopenia in humans, none have to date proven effective 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A shift in MHC isoform distribution of this nature could contribute to reduced exercise tolerance given the differing oxidative potential of MHC I and II fibers and this has been demonstrated in patients (Vescovo et al, 1998). However, this pattern of isoform distribution is also emblematic of muscle disuse (Narici and De Boer, 2011) and heart failure patients expend about half as many calories in volitional activity as healthy controls (Toth et al, 1997), suggesting that this adaptation might be due to inactivity accompanying the disease, rather than the disease process itself.…”
Section: Heart Failurementioning
confidence: 98%
“…The concentrations of intra-mitochondrial citrate synthase, total cytosolic creatine kinase (CK), skeletal muscle-specific CK (MM-CK) and lactate dehydrogenase (LDH) decrease in HF patients [18]. Notably, angiotensin-converting enzyme inhibition, an established therapeutic intervention with impact on survival and exercise performance in HF, seems to prevent the fiber type switch from type I to II in the skeletal muscle [31-33]. …”
Section: Histologic Changes Of Skeletal Muscle In Hfmentioning
confidence: 99%